Cystic Adventitial Disease of Popliteal Artery with Venous Aneurysm of Popliteal Vein: Two-Year Follow-Up after Surgery - Koki Takizawa; Hiroshi Osawa; Atsuo Kojima; Samuel J. K. Abraham; Shigeru Hosaka (Case Reports in Vascular Medicine)
We report a rare case of cystic adventitial disease of popliteal artery with venous aneurysm of popliteal vein. A 46-year-old woman had sudden-onset intermittent claudication and coldness in her right leg. The right-sided ankle-brachial pressure index (ABI) was 1.01, but peripheral arterial pulsation was decreased at knee venting position. Computed tomography revealed simple cystic lesion of the popliteal artery and stenosis of the arterial lumen in this lesion. The patient was treated by complete resection of the cystic adventitial layer of popliteal artery. A venous aneurysm of popliteal vein was revealed by intraoperative echo and was simply ligated. The patient had uneventful postoperative course and no symptoms of relevance during the two years of follow-up.